2022
DOI: 10.1186/s13024-022-00572-6
|View full text |Cite
|
Sign up to set email alerts
|

Tau interactome and RNA binding proteins in neurodegenerative diseases

Abstract: Pathological tau aggregation is a primary neuropathological feature of many neurodegenerative diseases. Intriguingly, despite the common presence of tau aggregates in these diseases the affected brain regions, clinical symptoms, and morphology, conformation, and isoform ratio present in tau aggregates varies widely. The tau-mediated disease mechanisms that drive neurodegenerative disease are still unknown. Tau interactome studies are critically important for understanding tauopathy. They reveal the interacting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 126 publications
10
45
0
Order By: Relevance
“…However, despite the common Tau neuropathology, numerous studies have shown that Tau is processed distinctly in each of these conditions, which is reflected in differences in inclusion morphology, biochemical profile, and ultrastructure among the Tauopathies including PSP (Arakhamia et al, 2020;Falcon et al, 2019;Falcon, Zhang, Schweighauser, et al, 2018;Shi et al, 2021;Taniguchi-Watanabe et al, 2016). This is also supported by comparative interactome studies of human and rodent tau protein networks that show distinct differences in their aggresome profiles (Kavanagh et al, 2022), which potentially makes studying cellular mechanisms of the human condition difficult to recapitulate in rodent models.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the common Tau neuropathology, numerous studies have shown that Tau is processed distinctly in each of these conditions, which is reflected in differences in inclusion morphology, biochemical profile, and ultrastructure among the Tauopathies including PSP (Arakhamia et al, 2020;Falcon et al, 2019;Falcon, Zhang, Schweighauser, et al, 2018;Shi et al, 2021;Taniguchi-Watanabe et al, 2016). This is also supported by comparative interactome studies of human and rodent tau protein networks that show distinct differences in their aggresome profiles (Kavanagh et al, 2022), which potentially makes studying cellular mechanisms of the human condition difficult to recapitulate in rodent models.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an analysis to explore the differential proteome distributions across specific pathways/biofunctions revealed that most DEPs were related to changes in the adaptive immune system, the cellular response to chemical stress, programmed cell death or mitochondrial biogenesis. Our analysis also revealed that from the 484 dysregulated proteins, 8 proteins (including APOE 36 ) had been reported to functionally interact with tau and 27 proteins (including FUS 37 ) had also been found in the phosphorylated tau interactome of AD neurofibrillary tangles 27 . However, it is important to note that despite highlighting processes consistent with current concepts of neurodegenerative disease, a major limitation of the current approach is that we are unable to determine whether the observed changes in the proteome are related to the tau deposition.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, an analysis to explore the differential proteome distributions across specific pathways/biofunctions revealed that most DEPs were related to changes in the adaptive immune system, the cellular response to chemical stress, programmed cell death or mitochondrial biogenesis. Our analysis also revealed that from the 484 dysregulated proteins, 8 proteins (including APOE 36 ) had been reported to functionally interact with tau and 27 proteins (including FUS 37 ) had also been found in the phosphorylated tau interactome of AD neurofibrillary tangles 27 .…”
Section: Discussionmentioning
confidence: 58%
“…RPS27A has been linked to mild cognitive impairment (MCI) and AD [31, 32]. It has also been shown to interact with tau and lead to microglial activation that triggers subsequent widespread neurodegeneration [33, 34]. Both MRPL50 and NDUFB3 have been implicated in AD, glaucoma, and age-related neurodegeneration [35, 36].…”
Section: Discussionmentioning
confidence: 99%